Stabilization of aqueous graphene dispersions utilizing a biocompatible dispersant: a molecular dynamics study - Huang, Shirong; Croy, Alexander; Bezugly, Viktor; Cuniberti, Gianaurelio (Giovanni) (Physical Chemistry Chemical Physics, 2019)
Flavin mononucleotide sodium (FMNS) was recently reported as a highly efficient dispersant for the exfoliation of defect-free, few-layer, stabilized aqueous graphene dispersions. Most importantly, FMNS is innocuous and eco-friendly and can facilitate biomedical applications of graphene. Complementing those experimental studies, the influence of FMNS molecules on the aggregation behavior of graphene flakes in solution is investigated via all-atom molecular dynamics simulations. The stabilizing role of FMNS is demonstrated by the potential of mean force calculations for pairs of graphene flakes covered by FMNS molecules. These results indicate that the optimal amount ratio between FMNS molecules and carbon atoms in monolayer graphene is about 0.026 leading to a surface coverage of 0.34 FMNS molecules per nm2 on the graphene flakes. Overall the simulations support the high efficiency of FMNS as a surfactant compared to other surfactants.
CRIS-Team Scopus Importer:2022-04-14